2020
DOI: 10.22271/chemi.2020.v8.i3e.9251
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of nutritive composition of Sauropus androgynus (Multivitamin plant) at different growth stages and position of leaves

Abstract: A study was designed to estimate the nutritive composition of Chekkurmanis (Katuk) leaves on two different growth stages viz., 60 & 120 days after planting and two different positions viz., terminal and basal whorls in plants. Utilization of green leafy vegetables differs from leaves of annuals and shrubs to leaves of trees. Katuk leaves rich in vitamins and minerals are known as protective food. The results of the study showed that Vitamin C, Protein, Calcium, Carbohydrate contents increased with the growth s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…S. androgynus is also called a ‘multigreen vegetable’ because of its high nutritional value and vitamin quantity in comparison with other vegetable crops [ 6 , 60 ]. S. androgynus is a rich source of vitamin A and C, protein, calcium and carbohydrates in comparison with other leafy vegetables such as amaranth and drumstick leaves [ 61 ]. It has been proved that the concentration of water-soluble vitamins is higher in S. androgynus leaves than fat-soluble vitamins [ 62 ].…”
Section: Nutritional Valuementioning
confidence: 99%
See 1 more Smart Citation
“…S. androgynus is also called a ‘multigreen vegetable’ because of its high nutritional value and vitamin quantity in comparison with other vegetable crops [ 6 , 60 ]. S. androgynus is a rich source of vitamin A and C, protein, calcium and carbohydrates in comparison with other leafy vegetables such as amaranth and drumstick leaves [ 61 ]. It has been proved that the concentration of water-soluble vitamins is higher in S. androgynus leaves than fat-soluble vitamins [ 62 ].…”
Section: Nutritional Valuementioning
confidence: 99%
“…Studies reveal that they are also rich in fat-soluble vitamin E which have antioxidant properties [ 62 ]. A comparative study was performed to understand the difference between the nutritional composition of basal whorl leaves and terminal whorl leaves of S. androgynus by Naveena et al [ 61 ] and found that basal whorl leaves are more enriched with nutrients than terminal whorl leaves. They also reported that there was a significant elevation in the quantity of nutrients such as proteins, carbohydrates, calcium and vitamin C from day 60 to day 120 which suggests the difference in nutrient accumulation inside plant organs according to their developmental stages [ 61 ].…”
Section: Nutritional Valuementioning
confidence: 99%